Learning Management Strategies Using Wordwall to Enhance Collaboration Skills of Fifth Grade Madrasah Ibtidaiyah Students - Mualifin, Isnan; Sutarum; Machsunah, Yayuk Chayatun (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2025)
This study investigates the effectiveness of learning management strategies utilizing Wordwall, an interactive digital learning platform, in enhancing the collaboration skills of fifth-grade students in Madrasah Ibtidaiyah. A quantitative research design was applied with a total population of 45 students (29 male, 16 female). Data were collected through a Likert-scale questionnaire and analyzed using SPSS 26.0, including validity and reliability tests, the coefficient of determination (R²), and a t-test for significance. The findings revealed a significant positive effect of Wordwall-based learning management on students’ collaboration skills (R² = 0.608; p < 0.05). The t-test results indicated that the use of Wordwall significantly improved collaboration skills, confirming the acceptance of the alternative hypothesis. Wordwall’s integration into classroom learning fosters active participation, teamwork, and mutual respect among students. The findings support the adoption of digital learning management strategies to improve 21st-century collaboration competencies in Islamic elementary schools.